Tomoelastography for Measurement of Tumor Volume Related to Tissue Stiffness in Pancreatic Ductal Adenocarcinomas. Issue 12 (December 2020) - Marticorena Garcia, Stephan R.; Zhu, Liang; Gültekin, Emin; Schmuck, Rosa; Burkhardt, Christian; Bahra, Marcus; Geisel, Dominik; Shahryari, Mehrgan; Braun, Jürgen; Hamm, Bernd; Jin, Zheng-yu; Sack, Ingolf; et al.
Abstract : Objectives: Estimations of tumor volume and boundary in pancreatic ductal adenocarcinoma (PDAC) are crucial for surgery planning. The aim of the study is to evaluate tomoelastography for detection of PDAC and quantification of PDAC volume based on tissue stiffness. Materials and Methods: From March 2018 to December 2019, a total of 102 participants (30 healthy participants and 72 patients with histologically proven PDAC) were prospectively enrolled in a multicenter study. Multifrequency magnetic resonance elastography was combined with tomoelastography postprocessing to generate maps of shear wave speed (SWS) depicting highly resolved anatomical details of tissue stiffness. Subregional analysis of pancreatic head, body, and tail and reproducibility tests were performed in healthy participants, whereas tumorous (PDAC-T) and nontumorous (PDAC-NT) pancreatic tissue analysis was conducted in patients. In all patients, tumor volumes measured by computed tomography (CT) were compared with SWS-derived volumes. In addition, in 32 patients, tumor sizes were evaluated by macroscopy after resection. Results: Tumor volumes were quantified in 99% and 87% of all cases with tomoelastography and CT, respectively. Pancreatic SWS was highly reproducible (repeatability coefficient = 0.12) and did not vary regionally or with patient age, sex, or body mass index (all P > 0.08). Shear wave speed was higher in PDAC-T (2.08 ± 0.38 m/s) than in healthy (1.25 ± 0.09 m/s; P < 0.001) and PDAC-NT (1.28 ± 0.14 m/s; P < 0.001) participants. A threshold of 1.47 m/s separated PDAC-T from healthy volunteers (area under the curve = 1.0, sensitivity = 100%, specificity = 100%), while 1.49 m/s separated PDAC-T from PDAC-NT with high accuracy (area under the curve = 0.99, sensitivity = 90%, specificity = 100%). Tomoelastography-derived tumor volume correlated with CT volume ( r = 0.91, P < 0.001) and ex vivo tumor volume ( r = 0.66, P < 0.001). Conclusions: Tomoelastography provides a quantitative imaging marker for tissue stiffness depicting PDAC boundaries and separates PDAC from unaffected pancreatic tissue. Abstract : Supplemental digital content is available in the text.